Identifikasi Keberadaan Air pada Proses Penyaluran Fluida Produksi di Lapangan Minyak Lepas Pantai - Hariyadi Hariyadi; Dedy Kristanto; Yulius Deddy Hermawan (Eksergi, 2020)
Oil production that flows from the Platform to the FSO (Floating Storage and Offloading) "A" is derived from PT. "B" and the "C" Oil Company in the Madura Strait. The total oil production flowing from the Platform to the "A" FSO is currently around 6000 BOPD. As a result of the delivery system using the same channel, a problem arises, namely oil losses between the Platform as a delivery point and FSO "A" as a receiving point. Besides that, the water that is involved in the oil distribution process will be a deduction factor that will be used as a correction for oil shipments, the more water the less amount of oil will be received at FSO "A". The oil samples that have been taken are then observed for their characteristics, namely density, composition (%-mole), BS&W, emulsion, flash, shrinkage at PPPTMGB "Lemigas" Laboratory Jakarta. The specific gravity of samples is around 1,018. While the characteristics of the two are different from the characteristics of sea water; this difference is shown by the results of SG (1,018 vs 1,025) and the salt content of sea water is much higher than the water formation of PT "B" and PT "C". The oil samples of PT "B" and PT "C" have almost the same SG, which is 0.79. BS&W oil in both ships is quite low; this shows that the separation of oil and water on the Platform went quite well. However, BS&W samples in incoming FSO "A" are very high, at 5%; this indicates an off-set at the water-oil interface level settling time on the Platform separator so that water can be joined with the oil flow from the Platform to the FSO "A"